Islamist Extremism Ideology Rehabilitation Programs: A Critical Analysis - Abdul Rahim, Rahimin Affandi; Abdul Razak, Mohd Imran; Ramli , Mohd Anuar; Kahal, Siti Maimunah (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2021)
The September 11 attacks gave an immense impact on Muslims worldwide. Governments, both Islamic and Western took matters regarding terrorism even more seriously. The incident too, however, became a stepping stone for Muslim terrorists to be louder. Nevertheless, terrorism among Muslims have always existed in the doctrine of certain sects, Salafi Jihadi in particular. Such extreme and radical misconceptions of Islam is inherited by their predecessor, the Khawarij. The study discusses the rehabilitation programs for those affected by extremism in Malaysia, and the regional guidelines for counter terrorism. The root cause for Islamist extremism is also analysed, along with the influence of Khawarij ideology on Salafi Jihadi, the similarities shared by both, particularly with regards of jihad.